Disputes of issues of family affairs - Kechbat, Hanane; Lemtai, Noureddine (Journal of Human Sciences, 2022)
This paper the stresses the necessity to insight in family disputes and the scope of intervention of the judge in the proceedings through the provision of the code civil and administrative procedure.In this context we will ty to see some o these disputes family and how to exercise the family magistrate his power to resolve these disputes wich might reflect some of the actual.Problems of these conflicts in terms of substantive family law on the one hand on the other hand the procedural aspect of the code of civil and administrative procedure.First: we will try to addresse disputes of the provisions of the marriage and its procedures starting with his introductions and through the procedures of registration and proof of ending his effects.Second: we will try to addresse with the disputes related to the legitimate act of minors in addition to quarrels of stone and protection measures for adults who are unqualified.